Measurement of psi(2S) meson production in pp collisions at root s = 7 TeV - Aaij, R; Abellan Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; Alvarez Cartelle, P; et al. (2012)
The differential cross-section for the inclusive production of ψ(2S) mesons in pp collisions at √s = 7 TeV has been measured with the LHCb detector. The data sample corresponds to an integrated luminosity of 36 pb -1. The ψ(2S) mesons are reconstructed in the decay channels ψ(2S)→μ +μ - and ψ(2S)→J/ψπ +π -, with the J/ψ meson decaying into two muons. Results are presented both for promptly produced ψ(2S) mesons and for those originating from b-hadron decays. In the kinematic range p T(ψ(2S))≤16 GeV/c and 2